PENGEMBANGAN MODEL PEMBELAJARAN SHOOTING DALAM PERMAINAN BOLA BASKET - Indrayogi Indrayogi; Bhakti Muda Heryanto (Universitas Majalengka, 2019)
Indrayogi dan Bhakti Muda Heryanto Program Studi Pendidikan Jasmani, Universitas Majalengka indrayogi13@gmail.com Abstract This study aims to produce shooting learning models in basketball games to improve the ability of basic shooting techniques in basketball games through model development studies. This research method is a study that refers to the development model of Borg and Gall which has been varied, namely (1) conducting and initial research model, (2) making a new product in the form of a basketball shooting learning model, (3) learning expert validation and practitioner expert basketball, (4) conducted 16 small-scale trials of students, (5) product revisions by learning experts and basketball practitioner experts, (6) conducted a large-scale trial of 31 students, (7) product revisions based on large group trial activities. The final product development result from the final product revision are basketball shooting learning models. The data analysis technique used is descriptive percentages and qualitative analysis techniques. From the available data, it can be concluded that the development of basketball shooting learning models can be used in the learning process. Keywords : development, shooting learning model, basketball game Abstrak Penelitian ini bertujuan menghasilkan model pembelajaran shooting dalam permainan bola basket untuk meningkatkan kemampuan teknik dasar shooting dalam permainan bola basket melalui studi pengembangan model. Metode penelitian ini adalah penelitian yang mengacu pada model pengembangan dari Borg dan Gall yang telah divariasi, yaitu (1) melakukan penelitian model awal, (2) pembuatan produk baru yang berupa model pembelajaran shooting bola basket, (3) Validasi Ahli Pembelajaran dan Ahli Praktisi Basket, (4) melakukan uji coba skala kecil 16 siswa, (5) revisi produk oleh ahli pembelajaran dan ahli praktisi basket, (6) melakukan uji coba skala besar 31 siswa, (7) revisi produk berdasarkan kegiatan uji coba kelompok besar. Hasil akhir produk pengembangan dari hasil revisi produk akhir yaitu model pembelajaran shooting bola basket. Teknik analisis data yang digunakan adalah deskriptif persentase dan teknik analisis kualitatif. Dari data yang ada maka dapat disimpulkan bahwa pengembangan model pembelajaran shooting bola basket dapat digunakan dalam proses pembelajaran. Kata kunci : pengembangan, model pembelajaran shooting, permainan bola basket